Extensive Characterization of Mesenchymal Stem Cell Marker Expression on Freshly Isolated and In Vitro Expanded Human Adipose-Derived Stem Cells from Breast Cancer Patients - Premrutai Thitilertdecha; Visnu Lohsiriwat; Poonsin Poungpairoj; Varangkana Tantithavorn; Nattawat Onlamoon (Stem Cells International)
Variation in numbers and functions of cells in fat tissues may affect therapeutic outcomes and adverse events after autologous fat tissue grafting in postmastectomy breast cancer patients; however, the relevant information regarding cellular components is still incomplete. Phenotypic characterization of heterogeneous cell subsets in stromal vascular fraction (SVF) isolated from fat tissues by flow cytometry was also limited to a combination of few molecules. This study, therefore, developed a polychromatic staining panel for an in-depth characterization of freshly isolated SVF and expanded adipose-derived stem cells (ADSC) from the patients. ADSC were found predominant in SVF (~65% of CD45- cells) with a homogenous phenotype of CD13+CD31-CD34+CD45-CD73+CD90+CD105-CD146- (~94% of total ADSC). Endothelial progenitor cells (EPC) and pericytes were minor (~18% and ~11% of CD45- cells, respectively) with large heterogeneity. Downregulation of CD34 and upregulation of CD105 in ADSC were profound at passage 3, showing a phenotype similar to the classical mesenchymal stem cells from the bone marrow. Results from this study demonstrated that fat tissue collected from patients contains ADSC with a highly homogenous phenotype. The in vitro culture of these cells maintained their homogeneity with modified CD34 and CD105 expression, suggesting the expansion from a single population of ADSC.